Exploring Motivational Message and Literary Themes in Little Women (2019): A Masovian Perspective - Sadewi, Nurfadillah; Syamsurrijal, Syamsurrijal (CV Insan Kreasi Media, 2025)
This study examines the motivational themes and themes in Greta Gerwig's film, Little Women (2019), based on Louisa May Alcott's work, from a Maslowian perspective, focusing on how the adaptation of the novel relates to the interplay between power, desire, and masculinity, using Louisa May Alcott's experiences. Gerwig's adaptation also serves as a general example of using Maslow's hierarchy of needs in feminist novels. According to Maslow's theory, everyone has five needs: physiological, safety, social, esteem, and self-actualization. (Maslow, 2017). This provides a basis for analyzing motivation in the novel. The relationships and identities of each main character in